Was Bashar ibn Burd a Chaste Poet? - Hayyawi Al-Saad, Prof. Dr. Ahmad (Basra studies journal, 2025)
This research addresses the virgin odes of Bashar ibn Burd, which were overshadowed by his extreme satire and lascivious love poetry. Did Bashar truly love, or was his romantic poetry simply a mean of variety and challenge? This is what the research intend to answer through full study and analysis in the following pages.